"Rural Development Clubs" - an innovative platform for catalysing rural development - Sethi, K.S. (2003)
The process of technology adoption cannot be taken as a simplistic process like that of giving a pill to common man to revitalize him and pull him up above the poverty line. Instead, it is to be seen as an interactive process of education regarding the available alternatives, so that the rural communities are empowered to take informed decisions for their development. - Reproduced.
Keywords: Rural development